Formyl Peptide Receptors and Annexin A1: Complementary Mechanisms to Infliximab in Murine Experimental Colitis and Crohn’s Disease - de Paula-Silva, Marina; da Rocha, Gustavo Henrique Oliveira; Broering, Milena Fronza; Queiroz, Maria Luíza; Sandri, Silvana; Loiola, Rodrigo Azevedo; Oliani, Sonia Maria; Vieira, Andrea; Perretti, Mauro; Farsky, Sandra Helena Poliselli (Frontiers in Immunology, 2021)
Non-responsiveness to anti-TNF-α therapies presents relevant rates in inflammatory bowel disease patients, emerging the need to find biomarkers involved in therapeutic efficacy. Herein, we demonstrate that higher levels of colonic formyl-peptide receptor 1 and annexin A1 correlate with histological recovery in Crohn’s Disease patients under remission. Using the dextran sulphate sodium colitis model in mice, we suggest infliximab induces annexin A1 expression and secretion in activated intestinal leukocytes. Conversely, this mechanism might stimulate epithelial formyl-peptide receptors, inducing wound healing and consequent histological remission. Our data indicates that assessing formyl-peptide receptors and annexin A1 intestinal expression might provide precious information about disease activity and responsiveness to infliximab in inflammatory bowel disease patients.